PEMBELAJARAN ATAS TALIAN MAHASISWA PRASISWAZAH UNIMAS - Nur Zafirah, Mohamad Othman (Universiti Malaysia Sarawak (UNIMAS), 2020)
Online learning is crucial in the era of technological advancement for every public and private institution. This study examines online learning among undergraduate students of public institutions of higher learning. The main issue in this study is the problems faced by undergraduate students while undergoing online learning during the pandemic. There are three objectives for this study, namely, to study the advantages and disadvantages of online learning, the problems faced by undergraduate students on online learning and to research the level of performance of undergraduate students during online learning. The scope of this study is limited to UNIMAS undergraduate students. The method used in this study was a semi-structured interview and only three UNIMAS undergraduate students were selected to be respondents in this study. Data were collected using interview transcripts and each answer will be studied together with the objectives of the study as well as the problem statement in the study. The results of the study found that the main problem of undergraduate students is with regard to the internet network. This shows that it is important for each area to have an internet network so that online learning can run smoothly and does not affect student performance. The rapid growth of technology nowadays makes the use of the internet very important in education.